INVESTMENT INCENTIVES IN THE CZECH REPUBLIC - Dominika FALISOVÁ; Jozef GLOVA (Humanities and Social Sciences)
This study examines the effectiveness of investment incentives in the Czech Republic in reducing regional unemployment. Using correlation analysis, it investigates the relationship between job creation and unemployment rates across various Czech regions. The results reveal notable regional disparities: in the Central Bohemian Region, job creation is associated with lower unemployment while, in structurally affected areas such as Moravia-Silesia and Ústí, high job creation does not translate into lower unemployment due to factors such as skill mismatches and industrial decline. The Karlovy Vary Region shows particularly deep-rooted labor market challenges. The main contribution of this paper lies in demonstrating that investment incentives have inconsistent impacts and that their effectiveness is highly context dependent. These findings underscore the need for region-specific policy approaches that go beyond general job creation and directly address structural labor market weaknesses.